AUDIT OF ADVANCED LABORATORY INVESTIGATIONS - Pakra, Mohammad Saeed Al; Asghar, Abdul Shaheed; Khan, Amjad Ali; Kashif, Muhammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Advanced laboratory investigations at reference laboratories play a key role in the diagnosis of the disease, but misuse of this precious and expensive tool may misguide the physician in patient management. This study was carried out as an audit of investigations performed at a reference laboratory, in order to assess their cost effectiveness, to identify various errors, the degree of correlation of requested tests with the clinical diagnosis and benefit to the patients. Method: A four phase audit of 337 laboratory investigation prescription was performed from April 2012 to March 2013 in the Medical Administration in collaboration with Department of Medical Laboratory and various Clinics at the King Salman Armed Forces Hospital in Northwestern Region - Kingdom of Saudi Arabia. All the information was recorded on a questionnaire Performa. Results: On data compilation and analysis it was found that 174(51.63%) test results were within normal reference range, while 163 (48.37%) test results were reported as positive. Also 218 (64.69%) investigations results correlated with clinical assessment by the physician, while 119 (35.31%) investigation results did not correlate with the clinical assessment by the physician. The expenses incurred Euro 12868 were spent on non-correlated tests while on correlated tests were Euro 31831. In terms of benefit to the patients 243 (82.09%) patients were reported by clinicians to have benefited from the reference laboratory tests, while 53 (17.91%) cases did not benefit from the reference laboratory tests as assessed by the clinicians and 41 (12.16%) cases in which even clinician did not respond regarding the benefit to the patients. Three categories of errors were identified (26.40%), i.e., at the level of clinicians (12.75%), at the level of hospital lab (5.04%) and at the level of reference lab (8.60%).Conclusion: Thorough clinical assessment and judicious utilization of available preliminary laboratory tests are the keys to precise diagnosis and are instrumental in reducing reliance on reference laboratory investigations.